Heterogeneity analysis of PD-L1 expression and copy number status in EBUS-TBNA biopsy specimens of non-small cell lung cancer: Comparative assessment of primary and metastatic sites. (August 2019) - Yoshimura, Katsuhiro; Inoue, Yusuke; Karayama, Masato; Tsuchiya, Kazuo; Mori, Kazutaka; Suzuki, Yuzo; Iwashita, Yuji; Kahyo, Tomoaki; Kawase, Akikazu; Tanahashi, Masayuki; Ogawa, Hiroshi; Yokomura, Koushi; et al.
Highlights: Moderate concordance of PD-L1 expression between EBUS-TBNA and other specimens. Comparable concordance between PD-L1 copy number alterations and PD-L1 expression. PD-L1 expression was more intratumorally heterogeneous than PD-L1 copy number. Consider spatial heterogeneity when interpreting EBUS-TBNA-derived specimens. Abstract: Objectives: Most patients with non-small cell lung cancer (NSCLC) are diagnosed at advanced stages where small biopsy specimens obtained through endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) are sometimes the only available samples for diagnosis. We aimed to determine whether EBUS-TBNA specimens are suitable for the evaluation of PD-L1 protein expression and copy number alterations (CNAs). Materials and methods: PD-L1 protein expression and CNAs in 71 EBUS-TBNA specimens of NSCLC were assessed. Sixty-eight corresponding transbronchial biopsy (TBB) specimens from primary sites, thirteen resected primary tumors, and six resected metastases were comparatively analyzed. PD-L1 expression in tumor cells was assessed by immunohistochemistry (E1L3N). Positivity of ≥1% was used as the cutoff. PD-L1 CNAs were assessed with fluorescent in situ hybridization and were classified into three categories: amplification, polysomy, and disomy. Concordance between EBUS-TBNA and other specimens was calculated. Results: The cohort comprised 48 men (67.6%), 15 never-smokers (21.1%), and 39 adenocarcinomas (54.9%). The concordance of PD-L1 positivity between EBUS-TBNA and other specimens was moderate; κ = 0.63 for EBUS-TBNA vs. TBB, κ = 0.68 for EBUS-TBNA vs. resected primary tumors, and κ = 1.0 for EBUS-TBNA vs. resected metastases. The concordance of PD-L1 CNA status was comparable with that of PD-L1 expression: κ = 0.60 for EBUS-TBNA vs. TBB and κ = 0.74 for EBUS-TBNA vs. resected primary tumors. When PD-L1 copy number was assessed as a continuous variable, the correlation of PD-L1 CNAs was superior to that of PD-L1 expression. Intratumorally, PD-L1 copy number was less heterogeneous than protein expression in whole sections of resected tumors. Conclusion: EBUS-TBNA specimens can be used to assess PD-L1 CNAs and protein expression. Although spatial heterogeneity should be considered for accurate interpretation, the evaluation of PD-L1 CNAs provides more reproducible results than that of protein expression levels especially with regard to intratumoral heterogeneity.